Sensitivity comparison of immunofluorescent techniques for detection of rabies virus antigen from brain specimens - BEIGH, A B; SANDHU, B S; SINGH, C K; GUPTA, K; SOOD, N K (The Indian Journal of Animal Sciences, 2014)
The fluorescent antibody test (FAT) is most preferred method to visualize fine particles of rabies viral antigen in rabies infected tissues. In present study, formalin-fixed brain tissues from 100 clinically rabid animals were heat treated and tested for the presence of rabies virus antigen by direct immunofluorescent (IF) staining. The results were compared with those obtained from direct IF staining of acetone- fixed smears. The evaluation of rabies status between fresh and formalin – fixed tissue was in agreement in 100% of the cases. These results suggested that this technique is a valid procedure for routine diagnosis of rabies, particularly in situations in which fresh tissue is not available.